A golden chance for the party: The 10th National Congress of the Communist Party of Vietnam - Gerhard Will (Stiftung Wissenschaft und Politik (SWP), 2006)
Economic reforms during the past 20 years have brought high growth rates and modest prosperity to Vietnam. However, the limitations of those reforms are becoming more and more apparent. The 10th National Congress of the Communist Party of Vietnam (CPV), held in Hanoi from April 18 to 25, was therefore expected to deliver strategies and perspectives which could be used to overcome the challenges of the reform process. Whilst the Party Congress did produce some changes to a few key leadership positions, programmatically it fell back on old positions which fall short of answering the country's present societal and economic dynamics. (SWP Comments / SWP)
Keywords: 320